Implementation of the Campaign Prop Removal Policy during the Quiet Period of the 2024 Regional Head Election in Tanjungpinang City - Erny Simatupang; Alfiandri Alfiandri; Armauliza Septiawan (Social Science Academic, 2026)
This study examines the implementation of the campaign prop removal policy during the quiet period of the 2024 Regional Head Election in Tanjungpinang City. The issue is important because the quiet period is designed to protect voter autonomy, maintain electoral neutrality, and ensure fairness before voting day. The purpose of this study is to analyze how the policy was implemented, identify the actors involved, and explain the factors that influenced the gap between electoral regulation and field practice. This research employed a qualitative descriptive approach using secondary data, including regulations, institutional documents, field records, media reports, and visual documentation, analyzed through content analysis and the Van Meter and Van Horn policy implementation framework. The findings show that although the policy had a clear legal basis, campaign props were still found in several areas of Tanjungpinang City during the quiet period. The implementation gap was influenced by low compliance among campaign actors, limited personnel and time, weak inter-agency coordination, and insufficient early mapping of campaign prop locations. The study concludes that campaign prop removal should be strengthened through preventive mapping, formal notification, joint field monitoring, public reporting, enforcement follow-up, and post-election evaluation to support electoral order, neutrality, and local democratic integrity.